A Retrospective Study of the Association between Respiratory Tract Viral PCR Panel Results and Clinical Outcomes in Children with Cancer and Febrile Neutropenia and Review of the Literature - Terzi, Özlem; Karabulut, Nuran; Uysalol, Ezgi Paslı; Kaçar, Ayşe Gonca; Solgun, Hüseyin Avni; Ertürk, Saide; Şimşek, Halil İbrahim; Bayram, Cengiz; Ayçiçek, Ali (Journal of Pediatric Infectious Diseases, 2023)
Objective The role of respiratory viral pathogens (RVPs) in children with cancer having febrile neutropenic (FEN) episodes has not been well studied. The objectives of this study were to investigate the prevalence and clinical outcomes of RVP in this group.Methods Pediatric patients with cancer and an episode of FEN, presenting between March 2021 and March 2022 were included. All data were retrospectively retrieved from patient files. A throat swab sample was obtained for the detection of 17 RVPs and evaluated by a polymerase chain reaction (PCR) method.Results A total of 110 (male n = 76; 69.1%) patients with a mean ± standard deviation age of 6.68 ± 4.92 years were included. Reproduction in PCR was seen in 76 (69.1%) children. Rhinovirus (31.6%) and respiratory syncytial virus (15.8%) were the most frequently detected viruses. Mixed respiratory viruses (coinfections of ≥2 viruses) were only seen in 13%. The median (range) duration of hospitalization was 11 (2–143) days, and 8.2% of the children were admitted to the pediatric intensive care unit (PICU). The median (range) length of stay (LOS) in the PICU was 8 (1–100) days. Overall mortality rate was 3.6%. There was no significant difference in LOS in the hospital, rate of admission to PICU, LOS in the PICU, and the mortality rate between children with and without growth in PCR (p > 0.05).Conclusion There was high prevalence of RVP in children with cancer and FEN. However, given that having a positive RVP does not affect LOS in the hospital/PICU or disease severity, in this population, there was no association between positive PCR findings and clinical features investigated or outcome.
Keywords: febrile neutropenia; oncology; respiratory viral infection; children